A intimidade de Santa Teresa de Lisieux com Deus e seu reflexo na pastoral e na missão da Igreja - Schweizer, Élida Coelho Pereira (2015)
The work attempts to show the importance of doctrine and theology of Saint Therese of Lisieux for the Church and the world. The impact caused by the publication of Story of a Soul , in world terms, that led His Holiness, Pope Pius XI, to name it "the Darling child of the world". The chapters tend to show relevant aspects of your life, which one cannot be separated from her writings, and the experience of the God s Word who forged his spirituality and intimacy with God. The scope of the "little way", her "Scientia amoris", with the clear goal of evangelization of all to lead them to Christ. As the love in the heart of the Church aims even more the desire of evangelization to save souls for the beloved, fulfill realizing her apostolic desire. The depth of her Christological doctrine on intimacy with God took on the titles: Patron Saint of the Missions and Doctor of the Church and be loved and revered throughout the world